(3JWHjbGJ YedjI Ydi HQfGeL (BExcels - (3eUWai(B, (3WhjWjs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2018)
(3Je JCdja gPG GdcJGH HLRFjI GdeJcGedjf djchf eQLYG YdejG dOYe GdLGfH GdeYQaj aj eLGd GdJMdjd GdGMUGFj dOj GdHGMKjf hGdWdHI, MjK jTed GdLRA GdChd CSGSjGJ GdeYGjfI, Ke JbfjGJ eJbOeI aj JaQjZ GdGSJHGfI Ydi GdHQfGeL hJJHYgeG aUd dELQGA GdJMbb ef KHGJ COGI LeY GdHjGfGJ GdChdjI, hNJe gPG GdLRA (BExcel (3hHYO cd Pdc Je GdJWQb Gdi CSGdjH JfXje hYQV GdHjGfGJ Ke CSGdjH GdhUa HGSJNOGe HQfGeL HaUd dGNJHGQ GdaQhV dHjGfGJ eJZjQ aQOj(B. (3CeG GdLRA GdKGfj abO Je JNUjUg HTcd CSGSj dCSGdjH JMdjd HjGfGJ eJZjQjf Ch CcKQ , HOC ef JMdjd GdJHGjf dCcKQ ef eLehYJjf eSJbdJjf (B(ANOVA) (3GdCMGOj hGdeJYOO, hcPG CSGdjH JMdjd GdJHGjf ddbjGSGJ GdeJcQQI hGdJj jJe GddLhD GdjgG aj MGdI bjGe GdHGMK HJYQjV cd aQO ef CaQGO GdeLehYI dcd eSJhi ef eSJhjGJ GdeJZjQ GdeSJbd Ydi GdCbd eQI hGMOI, ceG Je GdJWQb HGdJaUjd Edi GSJNOGeGJ CSdhH JMdjd GdJHGjJ GdeTJQc (B(ANOVA).s
(3GdeQGLY U(B.285 (3GdedGMb U(B.271s
Keywords: (3GdEMUGA GdJMdjdjs